Development of Indonesian Language Teaching Materials Based on Google Classroom in Primary Schools - Halidjah, Siti; Pranata, Rio (Journal of Education Technology, 2021)
Online learning materials prepared by teachers are less attractive and unclear to students, so interesting materials and teaching materials are needed in the online learning process. This study aims to develop Google Classroom-based teaching materials suitable for Indonesian language learning in theme 3 sub-theme 1 for grade IV in elementary school. This type of research is development research that employs a modified ADDIE model with steps of analysis, design, and development. The level of validity of teaching materials is measured based on assessments by design experts, linguists, and learning experts. Meanwhile, the practicality of teaching materials was measured based on assessments by grade IV students and teachers of Public Elementary School. The design expert validation results present an average number of 4.6, which is categorized as very valid; meanwhile, the instructional video experts' validation results show an average of 4.75, which is also classified as very valid. Furthermore, the linguist and expert study video's validation results also showed very valid results at a mean of 4.35 and 4.65, respectively. In addition, the results of expert validation on e-book learning and instructional videos obtained an average score of 4.6 and 4.55, and these two numbers are classified as very valid. Finally, the teacher's practicality assessment of teaching materials obtained an average of 3.45 and is classified as very practical.